Architektura polskich instytucji GLAM w XXI wieku = Architecture of Polish GLAM institutions in the 21st century - Kruszewski, Tomasz (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Architecture in Poland has been experiencing a lively quantitative and qualitative growth in recent years. Following the spectacular business and commercial facilities, projects of cultural and scientific institutions are implemented defined as GLAM (galleries, libraries, archives, museums) in the English-language acronym. Currently, in most large cities we have a new library, while in others libraries have undergone a general renovation, which has significantly affected the social reception of the objects. One needs to ask in what extend the implemented architectural concepts create a coherent whole as a sign of our times and to what extend they remain imitation forms of global trends. Does Poland, on the hundredth anniversary of Polish independence, create an autonomous architectural style, as it did a century ago? This article discusses the above-mentioned considerations.
Keywords: instytucje kultury (budynki); biblioteka (budynek); muzeum; centra nauki i kultury; architektura polska; rewitalizacja bibliotek; cultural institutions (buildings); library (building); museum; Science and culture centers; Polish architecture; revitalization of libraries